Recent Trends of Students in IT Related Programs of Science and Engineering in Nepalese Universities - Giri, Moti Prasad; Panthi, Dinesh; Pant, Dinesh Raj; Jha, Kanhaiya (International Journal of Humanities, Education, and Social Sciences, 2025)
In the current digital world, Nepalese universities have given high priority on IT related programs in the domain of science and engineering. Also, changing the modern education system and curriculum in the Universities with global compatibility, Nepal cannot isolate itself from the current trends and technologies. The main objective of this paper is to discuss recent trends of students in some major IT related programs of science and engineering of graduate and undergraduate level in Nepalese universities, as well as the status of the students' performance in examinations in these programs.